2019
DOI: 10.3389/fendo.2019.00230
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Genetic Variants and Hyperuricemia Risk in Chinese Men

Abstract: Objective: Obesity/metabolic syndrome and hyperuricemia are clinically associated; however, the association of obesity/metabolic syndrome-related genetic variants with hyperuricemia is not clear. Therefore, we assessed this association in Chinese men diagnosed with hyperuricemia in comparison to a non-hyperuricemia group. Methods: We genotyped 47 single nucleotide polymorphisms (SNPs) previously identified to be associated with obesity or metabolic syndrome in 474 adult males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“… 8 In humans, an obesity-related genetic variant (rs545854) was associated with serum UA levels and the susceptibility to hyperuricemia. 9 Obesity at childhood was associated with an elevated level of serum UA at young adulthood. 10 However, the precise mechanisms contributing to elevation of uric acid in individuals with obesity are not very clear.…”
Section: Introductionmentioning
confidence: 97%
“… 8 In humans, an obesity-related genetic variant (rs545854) was associated with serum UA levels and the susceptibility to hyperuricemia. 9 Obesity at childhood was associated with an elevated level of serum UA at young adulthood. 10 However, the precise mechanisms contributing to elevation of uric acid in individuals with obesity are not very clear.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, MsrA in tissues rather than the gut microbiota is a main contributor to sulindac activation. The association of genetic polymorphisms of human MSRA with obesity, diabetes, and coronary artery disease (Hotta et al, 2010;Yeung et al, 2011;Gu et al, 2013;Ma et al, 2019) has been reported, although studies assessing the impact of individual mutations on the enzymatic activity and/or expression of MSRA remain to be performed. It is worth investigating whether sulindac has excess or insufficient pharmacological effects in patients with MSRA variants.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, hyperuricemia was related to diabetes and high LDL-C in women only. Ma et al (2019) used multiplex polymerase chain reaction to genotype 47 SNPs already associated with obesity and MetS and discovered some were also associated with uric acid levels. The team adjusted for body mass index and central obesity and found the MSRA polymorphism rs545854 was an independent factor for the risk of HUA (OR = 2.81, 95% CI = 1.18–6.70, p = .0196).…”
Section: Literature Reviewmentioning
confidence: 99%
“…HUA and obesity together are associated with a significant risk of HTN (Tian et al, 2019). Ma et al (2019) assessed 8,331 participants in four groups in Liaoning province: normal body mass without HUA; obese (BMI > 25) without HUA; normal body mass with hyperuricemia; and obese with HUA. The obese-HUA group had a significantly elevated risk of HTN (OR 2.98 [95% CI: 2.48–3.57]) while the risk for those with HUA alone was barely altered (OR 1.14 [95% CI: 0.92–1.42]).…”
Section: Literature Reviewmentioning
confidence: 99%